MULTIVARIATE ANALYSIS AND CARTOGRAPHIC SYNTHESIS IN THE STUDY OF SOIL EROSION - Lima, Eduardo Rodrigues Viana de; Pinto, Sérgio dos Anjos Ferreira; Landim, Paulo Milton Barbosa (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2014)
This work aimed at evaluating the spatialization of the natural potential for soil erosion in the context USLE (The Universal Soil Loss Equation) by the multivariate statistics technique and the Geographic Information System (GIS) of a micro river basin located at the east portion of Paraíba estate. The erosion factor was created from geostatistical data analysis indirectly obtained in GIS environment. The erosion factors of rain and conservationist practice were considered regular for the area and manually inserted in GIS. Declivity and slope extension factors were manually obtained by topographic maps in 1:25.000 scales and also manually inserted in GIS. The soil use factor was obtained by visual interpretation of aerial photographs and manually inserted in GIS. The USLE formulation was applied in GIS to generate a map of potential for natural erosion and using the same USLE factors the statistic technique of multivariate factor analysis of the correspondences was used.  The achieved results showed that it is possible to use this statistic technique to integrate spatialization data originally used in mathematical formulations to generate synthesis map.